Syllable effects in beginning and intermediate European-Portuguese readers: Evidence from a sandwich masked go/no-go lexical decision task - Campos, Ana Duarte (2021)
Reading is one of the most important milestones a child achieves throughout development. Above the letter level, the syllable has been shown to play a relevant role at early stages of visual word recognition in adult skilled readers. However, studies aiming to examine when, during reading acquisition, the syllable emerges as a functional sublexical unit are scarce, and the studies conducted so far have led to inconsistent results. In this work, beginning and intermediate European-Portuguese (EP) developing readers performed a sandwich masked lexical decision task in which CV (e.g., RU.MOR[rumour]) and CVC (e.g., CIS.NE[swan]) first-syllable EP words were preceded either by syllable congruent (e.g., rum.ba-RU.MOR, cis.ra-CIS.NE), syllable incongruent (e.g., rum.ba-RU.MOR, ci.ser-CIS.NE), unrelated (e.g., va.cra-RU.MOR, zar.vo-CIS.NE) pseudowords primes, or identity (e.g., ru.mour-RU.MOUR, cis.ne-CIS.NE) primes. Results showed reliable syllable effects only for intermediate readers and for CV and CVC words alike. Findings are discussed attending to current models of visual word recognition.